2012
DOI: 10.4236/health.2012.49096
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effects of natural toothbrush (<i>Salva-dora persica</i>) in prevention of dental caries and plaque index

Abstract: Background: Nowadays, though more attention is being paid to oral and dental hygiene all over the world, dental caries and periodontal diseases are increasing daily. We decided to study the effectiveness of natural toothbrush in prevention of dental caries and plaque formation. Methods: This analytic, semi-experimental clinical trial included 390 individuals. Subjects were divided into 3 groups: using natural toothbrush, using artificial toothbrush and using both natural and artificial toothbrush. The plaque i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…It may further emphasized that the results of this trial are in close proximity with the results of a previously reported literature by Bhambal et al[23], who also reported no significant difference in plaque and gingival scores between the miswak and toothbrush users. The increase in plaque scores of subjects using toothbrush has not been observed in any of the previous studies[23242526], only a single study has reported the superior cleaning action of chewing stick in comparison to nylon toothbrush that too only for interproximal surfaces. [25] As far as the antimicrobial actions of chewing stick is concerned, literature has shown that the risk of dental caries identified was 9.35 times more in subjects using toothbrush than those using chewing sticks.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It may further emphasized that the results of this trial are in close proximity with the results of a previously reported literature by Bhambal et al[23], who also reported no significant difference in plaque and gingival scores between the miswak and toothbrush users. The increase in plaque scores of subjects using toothbrush has not been observed in any of the previous studies[23242526], only a single study has reported the superior cleaning action of chewing stick in comparison to nylon toothbrush that too only for interproximal surfaces. [25] As far as the antimicrobial actions of chewing stick is concerned, literature has shown that the risk of dental caries identified was 9.35 times more in subjects using toothbrush than those using chewing sticks.…”
Section: Discussionmentioning
confidence: 94%
“…However, a few available evidences have reported the effectiveness of chewing sticks against modern toothbrushes. [ 23 24 25 26 27 ] None of these studies have followed the Consolidated Standards of Reporting Trials guidelines (CONSORT), whereas the current trial was based on these international guidelines and hence maintain to prove a more reliable slant.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several over the counter mouthwashs are available in Pakistan, and none of them contain miswak extract which has an established therapeutic remedy for the control of plaque and gingivitis. [3][4][5][6][7][8] This study strongly recommends the incorporation of miswak extract in local mouth washes not only because of its natural pharmaceutical oral health benefits, high fluoride content but for being a cheaper product for the population of any developing country having financial constraints and limited oral health care amenities. However, more controlled trials are needed to establish miswak as a therapeutic medicament both mechanically and chemically for the prevention and control of periodontal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…2 The mechanical oral cleansing practices involve toothbrushes with dentifrices, however, chewing sticks or miswak has now proven its significant competence against effective plaque removal and gingival health. [3][4][5][6][7][8] Miswak is now in its recompensing phase. Laboratory examinations have established that many favorable natural ingredients are present in almost all types of miswak sticks which provide both systemic and local oral curative effects.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the number of S. mutants in saliva decreased significantly, but there was no significant difference in lactobacilli bacteria (Almas and Al-Zied, 2004;Fatin et al, 2012). Similarly, Wolinsky et al (1996) also showed that S. persica reduced the strength of specific colonization of Streptococci on tooth surfaces (Ezoddini-Ardakani et al, 2012).…”
Section: Antimicrobial Effect Of Miswakmentioning
confidence: 94%